The Analysis of Spatial Pattern and Hotspots of Aviation Accident and Ranking the Potential Risk Airports Based on GIS Platform - Yafei Li; Chen Liang (Journal of Advanced Transportation)
Aviation accident analysis is an important task to ensure aviation safety. The existing researches mainly focus on the analysis of aviation accident time characteristics and accident causes and less analysis of the spatial characteristics of aviation accidents. The spatial characteristics analysis of aviation accidents can identify hot spots of aviation accidents, improve the accuracy of aviation accident emergency management, and provide decision support for airport route planning. This study established the severity index of aviation accident based on aviation accident data, using GIS spatial analysis methods to study the spatial distribution characteristics of aviation accidents. The hot spots were identified in the aviation accidents. Finally, airports around the accident hot spots were ranked to obtain the airports with high potential aviation risks based on RI, taking Florida as an example. It was found that in the Florida aviation accident, general aviation accidents accounted for the majority, but the aviation accident severity index for air route flight was far greater than general aviation accidents. From the spatial distribution point of view, accidents with high severity index were distributed around large international airports. The Density Center for Aviation Accidents was located in Tampa, Miami, and some airports link areas in Florida. In terms of the Moran’s I index, the distribution of aviation accidents tended to aggregate in the region as a whole. However, aviation accident severity index was randomly distributed for each year separately. At the level of significance of 0.01, there were a total of 75 accident hotspots in the Florida region, mainly in the north and southwest. Airports with high RI in the Florida area were mainly concentrated in the Miami area and the Tampa Bay area, and Orlando Airport was ranked outside the top 10.